Meningkatkan Kemampuan Berhitung di SDN Kebon Pala 04 Pagi Melalui Pembelajaran Berbasis Game - Hidayatun, Fahmi; Supardi (Zona Education Indonesia, 2025)
This study aims to improve elementary school students’ numeracy skills through the implementation of game-based learning at SDN Kebon Pala 04 Pagi. Numeracy is one of the essential basic competencies in education; however, results from the National Assessment indicate that Indonesian students, particularly at the elementary level, still demonstrate low numeracy proficiency. This research employed a Classroom Action Research (CAR) approach, conducted in two cycles involving planning, implementation, observation, and reflection. Educational games such as number puzzles, interactive quizzes, and both digital and manual counting games were used to support the learning process. The findings revealed a significant improvement in students’ average scores, from 60.5 in the pre-test to 72.3 in the first cycle, and 81.7 in the second cycle. The percentage of students achieving the Minimum Mastery Criteria (MMC) also increased substantially from 40% to 75%. Moreover, game-based learning positively impacted students’ motivation and attitudes toward mathematics. The reflection process in each cycle enabled continuous refinement of learning strategies to make them more adaptive and effective. Therefore, game-based learning proves to be an enjoyable, interactive, and effective alternative strategy for enhancing numeracy skills among elementary school students